Phylogenetic systematics perspective and problems with ancestral species - theoretical considerations - Kaszycka, Katarzyna A. (Polskie Towarzystwo Antropologiczne, 1999)
The paper summarizes the main assumptions and procedures of phylogenetic systematics (cladistics), and presents problems with identifying common ancestral species from this perspective